Analisis Environmental Kuznets Curve pada PDRB Sektoral terhadap Emisi Gas Rumah Kaca di Provinsi Jawa Timur Tahun 1990-2022 - Naafia Fatiha Nur Insani; Mulyo Hendarto Robertus (Universitas Diponegoro, 2024)
East Java has the highest GDP value in the tertiary sector. According to the Environmental Kuznets Curve (EKC), economic growth in the tertiary sector should lead to improvements in environmental quality. However, the high value of greenhouse gas emissions indicates a decline in environmental quality. This research aims to analyze the EKC for the primary sector GDP, secondary sector GDP, and tertiary sector GDP in relation to greenhouse gas emissions. The time series data from 1990 to 2022 were sourced from the Badan Pusat Statistik and the Ministry of Environment and Forestry. The Ordinary Least Square (OLS) method was used. The results showed that the primary sector GDP and tertiary sector GDP had a positive and significant effect on greenhouse gas emissions. The secondary sector GDP had a negative and significant effect on greenhouse gas emissions. Overall, the effect was significant. The primary sector GDP and secondary sector GDP aligned with the EKC, while the tertiary sector GDP contradicted it. The inverted U-shape of the EKC did not occur. Despite the high contribution of the tertiary sector, there was a decline in environmental quality. Policy recommendations include maintaining environmental quality, particularly in relation to greenhouse gas emissions, in both the primary and tertiary sectors.